Is the Autism Boom Headed for Medicaid? Patterns in the Enrollment of Autistic Adults in Wisconsin Medicaid, 2008–2018. Issue 10 (17th July 2019) - Rubenstein, Eric; Bishop, Lauren
Abstract : Our primary objective was to describe demographic characteristics and enrollment patterns in a unique 11‐year full sample of adult Wisconsin Medicaid beneficiaries with identified autism spectrum disorder (ASD) or intellectual disability (ID). We obtained de‐identified Medicaid claims data for adults with a recorded ASD or ID diagnosis aged 21 and older with any Medicaid fee‐for‐service claims between January 1, 2008 and December 31, 2018. We assessed enrollment, age, number of visits, and paid amount per year using generalized linear models with a random intercept for each beneficiary. We identified claims for 4, 775 autistic adults without ID, 2, 738 autistic adults with ID, 14, 945 adults with ID, and 3, 484 adults with Down syndrome. The age distribution of the diagnostic group with ASD diagnoses was right skewed with a majority of beneficiaries less than age 30. The ASD without ID diagnostic group had the least visits and paid amount per person per year compared to other groups. In each age category, the ASD with ID diagnostic group had the most paid amount per person per year compared to other groups. It is urgent that we identify the health and health service needs of autistic adults from young adulthood through old age. Our findings have implications for ensuring adequate health coverage across the lifespan and highlight the importance of a strong and accessible health care system for autistic people. Autism Res 2019, 12: 1541–1550 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Medicaid provides health insurance to disabled people who meet income requirements. We assessed patterns of enrollment and service use among autistic adults and adults with developmental disabilities in Wisconsin Medicaid. We found a consistent influx of new young autistic adults without intellectual disability into the Medicaid system, with fewer visits and lower paid amounts compared to other developmental disability groups. The changing population of autistic people using Medicaid has implications for providing health care to autistic adults in the future.